“Loyal to Youth” – the history of the poetry magazine Kai based on the essay by Noriko Ibaragi - Wajs, Emilia (Silva Iaponicarum, 2026)
This article aims to examine the origins and principles of the Japanese poetry magazine Kai as detailed in Noriko Ibaragi’s (1926–2006) essay Kai Shōshi (‘a brief history of Kai’, 1969). The magazine, founded by Ibaragi and Hiroshi Kawasaki (1930–2004), emerged during the post-war era as a response to the ideological constraints that previously governed Japanese poetry. Kai distinguished itself from other literary magazines like Arechi and Rettō by emphasizing individuality, creative autonomy, and a break from traditional poetic forms. Ibaragi’s reflections in Kai Shōshi provide crucial insight into the magazine’s impact on postwar Japanese poetry, fostering a space for personal expression. This article contributes to the English-language scholarship by exploring the origins of Kai. In addition to discussing the historical and ideological context of the magazine’s foundation, this article presents and analyzes selected poems by Kai poets. These close readings illuminate the group’s poetic vision and their commitment to being accessible and socially engaged.